Wakaf Produktif Dalam Meningkatkan Ekonomi Ummat - Anwar Sadat; Yenni Juliati Samri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
wakqf is one of the economic instruments of the people that can be used for the economic empowerment of the people. Basically, waqf is productive in the sense that it must produce because waqf can fulfill its purpose if it has produced where the results are utilized in accordance with its designation (mauquf alaih) This research was conducted using a descriptive method with a qualitative approach based on data sources from literature study and observation. The purpose of this research is to provide information related to waqf management. The results showed that the application of productive waqf to improve Islamic economic welfare can be done with a variety of applications with development design models, including establishing mosques (places of worship), business shops, gas stations or gas stations, banking, offices, multi-purpose halls, photocopying, apartments or boarding houses, hotels, and others so as to achieve general benefits as a benefit for the people with social, economic and cultural development of the community.